PREVALENCE, MALE-FEMALE DIFFERENTIALS, AND FACTORS ASSOCIATED WITH OBESITY AMONG ADOLESCENTS IN ABUJA MUNICIPAL AREA COUNCIL (AMAC), NORTH-CENTRAL NIGERIA (Proceedings of the International Conference on Public Health, 2022)
Obesity among adolescents continues to rise in developing countries posing a major public health concern. This study investigated its prevalence and predictors among in-school adolescents. A school-based cross-sectional analytical study using multistage sampling to recruit 700 adolescents in Abuja Municipal Area Council (AMAC). Bodymass index (BMI) was measured at 18.5 - 30 for Obese and compared with the WHO BMI-for-age-z scores for age and samesex categorization. Eating patterns and Physical activity was measured using a valid questionnaire checklist. Data analysis employed descriptive and inferential statistics at p
Keywords: obesity, overweight, adolescents, eating pattern, physical activity